2010
DOI: 10.2174/1874941001003010032
|View full text |Cite
|
Sign up to set email alerts
|

Absinthe, Absinthism and Thujone - New Insight into the Spirits Impact on Public Health

Abstract: Absinthe, a strong alcoholic aperitif, is notorious for containing the compound 'thujone', which has been commonly regarded as its 'active ingredient'. It has been widely theorized that the thujone content of vintage absinthe made it harmful to public health, and caused the distinct syndrome absinthism, which was extensively described in the literature prior to the spirit's ban in 1915. The interdisciplinary research presented in this paper shows that 1) absinthism cannot be distinguished from common alcoholis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The only issue was that the dose-response relationship was largely neglected, as later investigations have shown that the wormwood content in absinthe was so negligible that the "no-effect level" in animal experiments with additional safety factors would not have been exceeded by even excessive human absinthe ingestion (Lachenmeier et al, 2008). The most plausible hypothesis today is that absinthism was just misdiagnosed alcoholism, as ethanol alone can explain all of absinthe's alleged effects (Strang et al, 1999;Padosch et al, 2006;Lachenmeier et al, 2010).…”
Section: The Rise and Fall Of Absinthementioning
confidence: 99%
“…The only issue was that the dose-response relationship was largely neglected, as later investigations have shown that the wormwood content in absinthe was so negligible that the "no-effect level" in animal experiments with additional safety factors would not have been exceeded by even excessive human absinthe ingestion (Lachenmeier et al, 2008). The most plausible hypothesis today is that absinthism was just misdiagnosed alcoholism, as ethanol alone can explain all of absinthe's alleged effects (Strang et al, 1999;Padosch et al, 2006;Lachenmeier et al, 2010).…”
Section: The Rise and Fall Of Absinthementioning
confidence: 99%
“…Commercially available sources of thujones revealed that the proposed samples contain both thujones in varying proportions, and contaminated with some camphor and fenchone. On the other hand, α‐thujone 1 and β‐thujone 2 are valuable epimeric chiral monoterpene ketones that are found in varying amounts in many crude essential oils (EOs) .…”
Section: Introductionmentioning
confidence: 99%
“…Wormwood may contain the bicyclic monoterpene ketone thujone [1]. In recent years there is a discussion in the literature regarding the actual thujone content in alcoholic beverages and its impact on public health as it is often associated with the syndrome absinthism [2]. An overview of history, toxicity, and analytics of absinthe was recently provided by Lachenmeier et al [1].…”
Section: Introductionmentioning
confidence: 99%